From pollution to sustainable environment: unlocking the role of energy intensity and renewable energy in highly pollutant nations - Zhi Zhen Zhou; Muhammad Shahid Hassan; Muhammad Ibrahim Saeed; Haider Mahmood; Rukhsana Kalim; Amira Houaneb (Environmental Research Communications)
Environmental degradation is among one of the most critical issues of recent times. To address this critical challenge in highly pollutant nations, this research inquires about the role of Energy Intensity (EI) along with Renewable Energy Consumption (REC) and non-REC as controlling indicators in the carbon emissions’ model. The research is significant because it provides potential information to energy policymakers for mitigating the adverse effects of environmental degradation. The Cross-Sectional Dependent (CSD) test is utilized to authenticate the CSD in the variables and the Slope Heterogeneity (SH) test is applied to verify the heterogeneous relationships across the polluted economies. Moreover, CSD-based unit root tests are applied to confirm the stationarity of the series. The CSD-based cointegration test is applied, which cares for both CSD and SH in analysis. Lastly, CSD-based regressions are applied to find the long and short relationships. A period of 1990–2021 is utilized for data analyses as per data availability of all analyzed countries. The results demonstrate significantly increasing effects of EI on emissions leading to mitigated environmental quality. A 1% increase in EI increases emissions by 0.6227%. However, renewable energy significantly mitigates carbon emissions while non-REC is found to significantly escalate carbon emissions. A 1% increase in REC mitigates emissions by 0.2458% and a 1% increase in non-REC raises emissions by 0.65%. This research further confirms the evidence of the Environmental Kuznets Curve (EKC) with an income elasticity of 13.1393 and income square elasticity of -0.6209. The results of EI, REC, and non-REC are similar in all estimations while the validity of the EKC is witnessed in two out of three models. The causal relation suggests feedback between emissions and economic progress, EI, REC, and non-REC, which highlights the interdependence of the energy sector and environmental outcomes. This research suggests that governments of the investigated polluted economies should impose taxes on non-renewable energy consumption. The revenues from these taxes should be utilized to subsidize renewable energy consumption. Both initiatives would help reduce energy intensity in these polluted economies to condense the environmental consequences of the energy sector.